Assessing Computational Fractional Flow Reserve From Optical Coherence Tomography in Patients With Intermediate Coronary Stenosis in the Left Anterior Descending Artery. (August 2016) - Ha, Jinyong; Kim, Jung-Sun; Lim, Jaeyeong; Kim, Gihoon; Lee, Seungwan; Lee, Joon Sang; Shin, Dong-Ho; Kim, Byeong-Keuk; Ko, Young-Guk; Choi, Donghoon; Jang, Yangsoo; Hong, Myeong-Ki
Abstract : Background—: Intravascular optical coherence tomography (OCT) imaging provides limited information on the functional assessment of coronary stenosis. We evaluated a new approach to OCT image–based computation modeling, which can be used to estimate the fractional flow reserve (FFR) in patients with intermediate coronary stenosis. Methods and Results—: Ninety-two patients with intermediate diameter stenosis in the left anterior descending artery underwent both FFR measurement with pressure wires and OCT examination. Using the OCT data, a computational fluid dynamics algorithm was used to calculate the computational FFR (FFROCT ). The diagnostic performance of the FFROCT was assessed based on the pressure wire–based FFR. The median FFR and FFROCT values were 0.86 (0.79–0.89) and 0.89 (0.82–0.94), respectively. The average diameter stenosis in quantitative coronary angiography and area stenosis in OCT were 58.1±13.4% and 67.5±13.5%, respectively. The FFROCT was better correlated to the FFR than were the anatomic variables ( r =0.72; P <0.001 versus r =0.46; P <0.001 for minimal luminal diameter on quantitative coronary angiography or r =0.57; P <0.001 for minimal lumen area on OCT). When functionally significant stenosis was defined as an FFR cutoff value of ⩽0.8, FFROCT resulted in 88.0% accuracy, 68.7% sensitivity, and 95.6% specificity. The positive and negative predictive values were 84.2% and 89.0%, respectively. Conclusions—: The computation of FFROCT enables assessment not only of anatomic information, but also of the functional significance of intermediate stenosis. This measurement may be a useful approach for the simultaneous evaluation of the functional and anatomic severity of coronary stenosis. Abstract : Supplemental Digital Content is available in the text.